“ Difficult but worth it”: Exploring the Experiences of Women in Engineering during Co-op - Arthur , Brittany; Guy, Batsheva; Armitage, Evie; Labarre, Meaghan; O'Connor, Sydney (Experiential Learning and Teaching in Higher Education, 2022)
None provided